Process manufacturing of functional food particles from lignin-rich feed - Huscroft, James Christopher (2020)
The aim of the work presented in this thesis was to investigate various manufacturing routes to create hydrophobic particulate emulsifiers from lignin-rich by-products. In turn creating a functional material from ordinary waste materials. Lignin, the second most abundant natural polymer after cellulose, is found in many different feedstocks. These are generated at multiple stages of food and drink production. Lignin provides structural support to the plant cell wall. Brewers’ Spent Grain (BSG) which, was milled and dried, was used as the chosen lignin-rich feedstock for conversion into particulate emulsifiers. Differential Scanning Calorimetry (DSC) was used to register the thermal transition of the lignin in the BSG prior to hydrothermal processing. Ordinarily, an Acetyl Bromide Soluble Lignin assay is used to quantify lignin content in a biomass, however here a newly devised solid state Nuclear Magnetic Resonance (NMR) method was used to calculate lignin content based on carbon resonance ratios in the produced spectrum. This is compared to the standard Acetyl Bromide Soluble Lignin assay as well as a known Thermogravimetric Analysis (TGA) method to allow for a three way comparison using different quantification techniques. Hydrothermal processing was used as a route to relocate lignin to the surface of the particulate emulsifier in the form of droplets. This in turn changed the particle hydrophobicity. In order to achieve this relocation, the feedstock requires processing above the quantified lignin transition temperature whereby the lignin undergoes a physical phase transition and as a result of cell wall collapse migrates through the to the surface of the particles. Numerous temperatures either side of this point of reference were tested and the highest temperature and time condition was found to have the greatest effect on the production of droplets. Scanning Electron Microscopy (SEM) was used to confirm the production of droplets and their composition was quantified with NMR. Particle size of particulate emulsifiers is crucial for production of emulsions and the size of the droplets produced. Methods of particle size reduction i.e. high pressure homogenisation did not generate particles which were in the order of magnitude desired (<10µm). Although particle size reduction did occur, this was as a result of removing primary cell wall constituents during the high pressure process. This removal proved critical in generating a greater number of droplets at the surface of a smaller particle once they were hydrothermally treated. Droplet coated particles have been shown to produce water-in-oil emulsions whereas the untreated feedstocks produced oil-in-water emulsions. As such, the newly created particles in this work will enable the formation of a range of emulsions with varying concentrations of oil and water in their composition.